2021
DOI: 10.1021/acsami.1c05884
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Flame Retardants of a P–N-Rich Polyphosphazene Elastomer Nanocoating on Cotton Fabric

Abstract: Modification by intumescent flame retardants is an effective way to impart antiflame properties to fabric materials. Polyphosphazene elastomers contain all three elements required by intumescent flame retardants: an acid source, a gas source, and a carbon source, making them all-in-one integrated intumescent flame retardants. In this work, halogen-free poly­(dimethoxy)­phosphazene (PDMP) loaded with 29.0 wt % phosphorus and 13.1 wt % nitrogen is shown to be an ideal flame retardant for fabric materials. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(20 citation statements)
references
References 30 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…15,16 The cyclic phosphazene group offers extraordinary intrinsic properties, such as natural flame retardancy and thermal stability. 17 Most of the preparation methods involving HCCP are based on solution polymerization, and only a few studies have been dedicated to synthesizing polyphosphazene films with IP. [13][14][15][16]18 Maaskant et al reported that the interfacial polycondensation of HCCP with diphenols in conventional IP is too slow to allow for ultrathin (∼10 8 m) film formation.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The cyclic phosphazene group offers extraordinary intrinsic properties, such as natural flame retardancy and thermal stability. 17 Most of the preparation methods involving HCCP are based on solution polymerization, and only a few studies have been dedicated to synthesizing polyphosphazene films with IP. [13][14][15][16]18 Maaskant et al reported that the interfacial polycondensation of HCCP with diphenols in conventional IP is too slow to allow for ultrathin (∼10 8 m) film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Cotton fabrics, as one of the most popular natural textiles, have been extensively applied in the clothing, packaging, industry, medical, and home textile markets by virtue of their excellent renewability, nontoxicity, breathability, and superior mechanical properties. However, the high flammability arising from their intrinsic chemical composition is a major disadvantage of cotton fabrics, which makes them prone to be easily ignited, with a high flame spread rate. The hidden fire hazards of cotton fabrics have seriously threatened the safety of human life and property over years. , Thus, there is an increasing demand to improve the flame retardancy of cotton fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…While cyclophosphazene nanospheres (PZS), with unique alternating P=N skeletons, are widely used in flame retardant materials due to their good compatibility and excellent flame retardancy. [27][28][29] Some studies on phosphazene-coated nanosheets, nanospheres or nanorods to enhance the flame retardancy of polymers have been widely reported. [30][31][32][33][34][35] Phosphazenes synergistically interact with inorganic nanoparticles to increase flame retardancy of materials.…”
Section: Introductionmentioning
confidence: 99%